Stéphan Barron : Art Planétaire = Earth Art. - Barron, Stephan; Maes, René (Tourcoing : École Régionale Supérieure d'Expression Plastique de Tourcoing.)
The CD-rom contains a multimedia presentation of Earth - and video-art works by Stéphan Barron creator between 1984 and 1998. It includes his writings on art, technology and ecology, as well as his doctoral thesis Earth Art and Techno-Ecological Romanticism.
Engels
Frans
boek
Keywords: Barron, Stephan